2007
DOI: 10.1042/bst0351278
|View full text |Cite
|
Sign up to set email alerts
|

Liprin-α proteins: scaffold molecules for synapse maturation

Abstract: Synapses are specialized communication junctions between neurons whose plasticity provides the structural and functional basis for information processing and storage in the brain. Recent biochemical, genetic and imaging studies in diverse model systems are beginning to reveal the molecular mechanisms by which synaptic vesicles, ion channels, receptors and other synaptic components assemble to make a functional synapse. Recent evidence has shown that the formation and function of synapses are critically regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 48 publications
1
106
0
Order By: Relevance
“…Notably, in the hierarchy of active zone assembly, genetic analysis in C. elegans has placed Syd-1 upstream of Syd-2 (Liprin-α), a protein linked to long-range transport of vesicular axonal cargo 27,28 . We previously found that Liprin-α localization was severely disturbed in Syd-1 mutants and proposed that Syd-1 might anchor clusters of Liprin-α 5 .…”
Section: Syd-1 Retains Liprin-a and Nrx-1 At Synapsesmentioning
confidence: 99%
“…Notably, in the hierarchy of active zone assembly, genetic analysis in C. elegans has placed Syd-1 upstream of Syd-2 (Liprin-α), a protein linked to long-range transport of vesicular axonal cargo 27,28 . We previously found that Liprin-α localization was severely disturbed in Syd-1 mutants and proposed that Syd-1 might anchor clusters of Liprin-α 5 .…”
Section: Syd-1 Retains Liprin-a and Nrx-1 At Synapsesmentioning
confidence: 99%
“…Other components of the same cortical assembly are the scaffolding proteins liprin-a1 and b1, a coiled-coil adaptor ELKS/ERC1, and the kinesin-4 KIF21A (Lansbergen et al, 2006;van der Vaart et al, 2013). Both liprins and ELKS are best known for their role in organizing presynaptic secretory sites (Hida and Ohtsuka, 2010;Spangler and Hoogenraad, 2007); in agreement with this function, ELKS is required for efficient constitutive exocytosis in HeLa cells (Grigoriev et al, 2007(Grigoriev et al, , 2011. LL5b, liprins and ELKS form micrometer-sized cortical patch-like structures, which will be termed here cortical microtubule stabilization complexes, or CMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…At the presynaptic terminals, the interaction of liprinα with the active zone proteins RIM and ELKS/CAST enhances presynaptic assembly and neurotransmitter release (12,13). At the postsynaptic sites, liprinα regulates the synaptic targeting of AMPA-type glutamate receptors through its interaction with GRIP (6,14); likewise, it regulates the trafficking of the cadherin-catenin adhesion protein complex through its interaction with the LAR family of receptor protein tyrosine phosphatases (15). Nevertheless, the molecular control that regulates the function of liprinα remains unclear.…”
Section: Cdk5-dependent Phosphorylation Of Liprinα1 Mediates Neuronalmentioning
confidence: 99%
“…The liprinα family comprises abundant scaffold proteins that have been suggested as being critical for synapse organization through their interactions with multiple synaptic proteins (6). At the presynaptic terminals, the interaction of liprinα with the active zone proteins RIM and ELKS/CAST enhances presynaptic assembly and neurotransmitter release (12,13).…”
Section: Cdk5-dependent Phosphorylation Of Liprinα1 Mediates Neuronalmentioning
confidence: 99%
See 1 more Smart Citation